1983
DOI: 10.1002/eji.1830130703
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for macrophages or for macrophage‐ or T cell‐derived factors in the mitogenic stimulation of murine B lymphocytes by lipopolysaccharides

Abstract: Splenic B cells from a variety of mouse strains could be depleted of accessory cells by removal of large cells through velocity sedimentation, followed by adherence to plastic and by passage over Sephadex G-10. Such accessory cell removal abolished the reactivity of the splenic B cells to the mitogen lipopolysaccharide (LPS), as measured by their capacity to polyclonally proliferate and mature to IgM-secreting cells. Accessory cells from different sources, such as peritoneal exudate cells, irradiated spleen ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…2). These results confirm earlier observations (10) showing that neither a factors, nor p factors, nor immunoglobulin-specific antibodies alone are sufficient for initiation and completion of the next cell cycle after mitosis.…”
supporting
confidence: 92%
“…2). These results confirm earlier observations (10) showing that neither a factors, nor p factors, nor immunoglobulin-specific antibodies alone are sufficient for initiation and completion of the next cell cycle after mitosis.…”
supporting
confidence: 92%
“…11 Earlier in vitro studies suggested that the TI B-cell response in mice to TNP-haptenated antigens such as TNP-Ficoll, TNPlipoprotein (LP), and TNP-Brucella abortus directly required macrophages. [12][13][14][15] Interestingly, interleukin 1 (IL-1) appeared to substitute for the requirement of macrophages in B-cell responses to TI antigens. In addition, IL-1-secreting cells reconstitute the response of macrophage-depleted splenic cells to TI antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, as a source of costimulatory signals, are essential for the generation of robust proliferation of B and T cells (7). It is therefore not surprising that they appear to be primary targets for factors modulating lymphocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing evidence supports a significant role for accessory cells in the activation of T and B cells both in vivo and in vitro (7,41). This has prompted numerous investigations into the role of macrophages in helminth-mediated immunomodulation of lymphocyte function (2,15,17,22,27,28,36).…”
mentioning
confidence: 99%